القيود الاجتماعية وعلاقتها بدافعية الإنجاز لدى طلبة المرحلة الإعدادية - الجميلي، محمد حميد سرحان ياسين (كلية الإمارات للعلوم التربوية, 2019)
استهدف البحث الحالي التعرف على القيود الاجتماعية وعلاقتها بدافعية الإنجاز لدى طلبة المرحلة الإعدادية، وقد تحدد مجتمع البحث الحالي بطلبة المرحلة الإعدادية لمديريات تربية بغداد (كرخ 1، كرخ2، كرخ 3) للعام الدراسي (2019- 2020)، وتألفت عينة الدراسة الحالية من (300) طالب وطالبة اختيروا بصورة عشوائية من المجتمع الأصلي، أما بالنسبة لأدوات البحث فقد قام الباحث باعتماد مقياس (Lepore& Ituarte, 1999) للقيود الاجتماعية والمعرب من قبل (جاسم، 2017)، ويتكون من (15) فقرة ذات تدرج رباعي (أبدا، نادرا، أحيانا، غالبا)، أما بالنسبة لمقياس دافعية الإنجاز اعتمد الباحث مقياس دافعية الإنجاز الذي أعدته (الرواف 2003) وهو يتكون من (39) فقرة ذات تدرج خماسي هي (تنطبق بدرجة كبيرة جدا، تنطبق بدرجة كبيرة، تنطبق بدرجة متوسطة، تنطبق بدرجة قليلة، تنطبق بدرجة قليلة جدا)، وقد استخرج الباحث مؤشرات الصدق والثبات للمقياسين، وتوصل البحث الحالي إلى النتائج الآتية: 1. يمتلك طلبة المرحلة الإعدادية مستوى متوسط من القيود الاجتماعية. 2. يمتلك طلبة المرحلة الإعدادية مستوى عالي من دافعية الإنجاز.. 3. ترتبط القيود الاجتماعية بدافعية الإنجاز بعلاقة عكسية، أي كلما قلت القيود الاجتماعية زادت دافعية الإنجاز. وقد وضع الباحث عدد من التوصيات والمقترحات على أساس النتائج التي خرج بها البحث الحالي.
The present research aimed at identifying the social constraints and their relation to the motivation of achievement among the students of the preparatory stage.The current research community has determined the students of the preparatory stage of Baghdad education directorates (Karkh 1, Kark 2, Kark 3) for the academic year (2019-2020), and the current study sample consisted of ( 300) Students were randomly selected from the original community. As for the research tools, the researcher adopted the scale (Lepore & Ituarte, 1999) of social restrictions and expressed by (Jassem, 2017), and consists of (15) paragraph with quadratic gradient (never, rarely As for the measure of achievement motivation, the researcher adopted a measure of motivation Injaz prepared by (Al-Rawaf 2003), which consists of (39) paragraph with a five-point gradient are (apply to a very large degree, apply to a large degree, apply to a medium degree, apply to a small degree, apply to a very small degree). The current research has reached the following results: 1. Middle school students have an average level of social restrictions. 2. The preparatory stage students have a high level of achievement motivation. 3. Social constraints are linked to the motivation of achievement an inverse relationship, ie the less social constraints the greater the motivation of achievement. The researcher has made a number of recommendations and proposals based on the results of the current research.
Keywords: طلبة المرحلة الاعداية -- القيود الاجتماعية -- الدافعية والانجاز -- التعلم والتعليم